Anti-inflammatory effects of the extract of Gnaphalium affine D. Don in vivo and in vitro. (24th December 2015) - Huang, Doudou; Chen, Yanhong; Chen, Wansheng; Liu, Ying; Yao, Fengyan; Xue, Dan; Sun, Lianna
Abstract: Ethnopharmacological relevance: Gnaphalium affine D. Don (GA) has been traditionally used as a medicinal herb in China for the treatment of many ailments including rheumatoid arthritis. However, the anti-arthritic mechanism of GA has still not been demonstrated. This study aims to reveal the anti-inflammatory activity and anti-arthritic mechanism of ethanol extract of G. affine D. Don. Materials and methods: Anti-inflammatory potential of GA was analyzed in vivo in carrageenan induced mice paw edema (acute study). Also, in vivo study was applied in collagen-induced arthritis (CIA) rats. In vitro experiments for analyzing the anti-inflammatory potential of GA were performed on rat alveolar macrophages cell line (NR8383). Analysis of nitric oxide release in NR8383 cells was done by Griess reaction. RT-PCR and western blotting experiment was performed to analyze the expression of phosphorylated p65 and IκBα/β-actin in NF-κB pathway. The production of TNF-α, IL-1β, and COX-2 in NR8383cells were measured by enzyme-linked immunosorbent assay. The chemical profile of GA was analyzed by HPLC-VWD. Results: GA significantly reduced the paw volume in carrageenan induced rat paw edema rat at different doses (300 and 600 mg/kg), compared with the standard indomethacin treatment. In CIA, GA can obviously ameliorate the inflammatory symptom, including cytokine, histological symptom and paw swelling. In the vitro study, GA was able to reduce the nitric oxide (NO) levels in NR8383 cells that had been stimulated with lipopolysaccharide (LPS). The level of TNF-α, IL-1β, and COX-2 was also decreased with GA treatment in NR8383 cells that had been stimulated with lipopolysaccharide (LPS). Interestingly, GA was found to decrease the level of phosphorylated p65 and IκBα in NR8383 cells. Fifteen compounds were identified by HPLC-VWD with the reference substances and verified by LC–MS. Conclusions: The results of the experiment scientifically validated its traditional use in inflammatory conditions. Graphical abstract: